A Critical Analysis of the Specific Pharmacist Interventions and Risk Assessments During the 12-Month TRANSAFE Rx Randomized Controlled Trial. Issue 6 (June 2022) - Gonzales, Haley M.; Fleming, James N.; Gebregziabher, Mulugeta; Posadas Salas, Maria Aurora; McGillicuddy, John W.; Taber, David J.
Background: Medication safety issues have detrimental implications on long-term outcomes in the high-risk kidney transplant (KTX) population. Medication errors, adverse drug events, and medication nonadherence are important and modifiable mechanisms of graft loss. Objective: To describe the frequency and types of interventions made during a pharmacist-led, mobile health–based intervention in KTX recipients and the impact on patient risk levels. Methods: This was a secondary analysis of data collected during a 12-month, parallel-arm, 1:1 randomized clinical controlled trial including 136 KTX recipients. Participants were randomized to receive either usual care or supplemental, pharmacist-driven medication therapy monitoring and management using a smartphone-enabled app integrated with telemonitoring of blood pressure and glucose (when applicable) and risk-based televisits. The primary outcome was pharmacist intervention type. Secondary outcomes included frequency of interventions and changes in risk levels. Results: A total of 68 patients were randomized to the intervention and included in this analysis. The mean age at baseline was 50.2 years; 51.5% of participants were male, and 58.8% were black. Primary pharmacist intervention types were medication reconciliation and patient education, followed by medication changes. Medication reconciliation remained high throughout the study period, whereas education and medication changes trended downward. From baseline to month 12, we observed an approximately 15% decrease in high-risk patients and a corresponding 15% increase in medium- or low-risk patients. Conclusion and Relevance: A pharmacist-led mHealth intervention may enhance opportunities for pharmacological and nonpharmacological interventions and mitigate risk levels in KTX recipients.